Impact of advance care planning for older adults with dementia in nursing homes - Koštomaj, Suzana (Obzornik zdravstvene nege, 2024)
Introduction: Advance care planning is a very important challenge in the field of palliative and hospice care. The aim of this study was to review empirical evidence on the effectiveness of advance care planning in palliative and hospice care for older adults with dementia, focusing on nursing home residents. Methods: The literature search was conducted in the PubMed, ScienceDirect and Scopus databases. The search terms included "advance care planning," "dementia," "palliative care," and "nursing home." The review included quantitative, qualitative and mixed-methods studies focussing on advance care planning for older adults with dementia published in English up to 2023. A narrative synthesis approach was used. Results: The review included a total of 10 studies. We identified two distinct concepts: advance care planning and empowerment of older adults with dementia. Discussion and conclusion: Our literature review revealed a clear relationship between the preferences expressed by older adults with dementia concerning their end-of-life care, their will to live and desire for less emotional distress at the end of life. Future research should employ a multidisciplinary approach to investigate the long-term impact and financial aspects of timely implementation of advance care planning, as well as appropriate strategies to empower its providers.
Keywords: advance directive; dignity; dostojanstvo; empowerment; opolnomočenje; paliativna oskrba; palliative care; vnaprejšnja direktiva